2018
DOI: 10.1111/micc.12454
|View full text |Cite
|
Sign up to set email alerts
|

Increase in perfused boundary region of endothelial glycocalyx is associated with higher prevalence of ischemic heart disease and lesions of microcirculation and vascular wall

Abstract: Thus, PBR can be considered a new highly reproducible and promising marker candidate for non-invasive diagnostics of IHD and cerebral atherosclerosis suggesting important role of microcirculation in development and progression of cardiovascular diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 28 publications
2
17
1
Order By: Relevance
“…Here, we show that CAD is accompanied by impaired sublingual microvascular perfusion, and that women with CAD, but not men with CAD, have reductions in microvascular glycocalyx barrier function. The magnitude of impaired sublingual microvascular barrier function in our female CAD patients relative to controls was similar to that observed in patients with end‐stage renal disease (Vlahu et al, ), lacunar stroke (Martens et al, ), ischemic heart disease (Gorshkov et al, ), and systemic sclerosis (Machin et al, ). A previous study showed that PBR was larger on average in patients with CAD compared to controls (Mulders et al, ).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Here, we show that CAD is accompanied by impaired sublingual microvascular perfusion, and that women with CAD, but not men with CAD, have reductions in microvascular glycocalyx barrier function. The magnitude of impaired sublingual microvascular barrier function in our female CAD patients relative to controls was similar to that observed in patients with end‐stage renal disease (Vlahu et al, ), lacunar stroke (Martens et al, ), ischemic heart disease (Gorshkov et al, ), and systemic sclerosis (Machin et al, ). A previous study showed that PBR was larger on average in patients with CAD compared to controls (Mulders et al, ).…”
Section: Discussionsupporting
confidence: 85%
“…This RBC accessible portion of the glycocalyx is commonly termed the perfused boundary region (PBR). A variety of cardiovascular diseases or risk factors, including end‐stage renal disease (Vlahu et al, ), lacunar stroke (Martens, Vink, Oostenbrugge, & Staals, ), ischemic heart disease (Gorshkov, Klimushina, Boytsov, Kots, & Gumanova, ), and systemic sclerosis (Machin, Gates, Vink, Frech, & Donato, ), have been associated with an increase of the sublingual microvascular PBR.…”
Section: Introductionmentioning
confidence: 99%
“…Values measured in our population (both “healthy” surgical and septic patients) were much lower. Interestingly, in recently published Russian population study [ 21 ] the PBR values corresponded much more with our own measurements; median and interquartile values were 1.9 (1.75-2.04) with values above 2 pointing towards increased cardiovascular risk. To which extent these differences in absolute values are affected by different SDF camera device (KK Research technology Ltd., UK, in ours and Russian study [ 21 ] vs. MicroVision Medical Inc., Wallingford, PA, in the Dutch study [ 12 ]) version of monitoring software (mostly not given) or population is to be further elucidated.…”
Section: Discussionsupporting
confidence: 84%
“…However, amount of data regarding the PBR is still too low to allow us for separation of clinically relevant changes. In our study the highest increase observed among septic responders was 8% which lies on the borderline of the coefficient of variation measured on our population (8%) or mentioned by other authors (less than 10%) [ 21 ]. The normal values in population have also not been evaluated yet.…”
Section: Discussioncontrasting
confidence: 77%
“…Therefore, an increased PBR may be viewed as an intermediate step between risk factors for atherosclerosis and cardiovascular events [57]. However, the correlations between PBR and risk factors and between PBR and cardiovascular events have not been consistently shown for the PBR: some studies have reported no clear association between the PBR and either vascular risk or vascular disease [4, 7], while others have found associations with atherosclerotic vascular disease [6, 8, 9]. These inconsistent findings might depend on the relatively small sample size of these studies and the focus on populations selected based on health status and of predominantly white ethnicity [46, 10].…”
Section: Introductionmentioning
confidence: 99%